Cardiac Arrest in Patients Managed for Convulsive Status Epilepticus: Characteristics, Predictors, and Outcome. Issue 8 (August 2018) - Legriel, Stephane; Bresson, Edouard; Deye, Nicolas; Grimaldi, David; Sauneuf, Bertrand; Lesieur, Olivier; Lascarrou, Jean-Baptiste; Argaud, Laurent; Chelly, Jonathan; Beuret, Pascal; Schnell, David; Chateauneuf, Anne-Laure; et al.
Abstract : Objectives: Cardiac arrest is a catastrophic event that may arise during the management of convulsive status epilepticus. We aimed to report the clinical characteristics, outcomes, and early predictors of convulsive status epilepticus–related cardiac arrest. Design: Retrospective multicenter study. Setting: Seventeen university or university affiliated participating ICUs in France and Belgium. Patients: Consecutive patients admitted to the participating ICUs for management of successfully resuscitated out-of-hospital cardiac arrest complicating the initial management of convulsive status epilepticus between 2000 and 2015. Patients were compared with controls without cardiac arrest identified in a single-center registry of convulsive status epilepticus patients, regarding characteristics, management, and outcome. Interventions: None. Measurements and Main Results: We included 49 cases with convulsive status epilepticus–cardiac arrest and 235 controls. In the cases, median time from medical team arrival to cardiac arrest was 25 minutes (interquartile range, 5–85 min). First recorded rhythm was asystole in 25 patients (51%) and pulseless electrical activity in 13 patients (27%). A significantly larger proportion of patients had a favorable 1-year outcome (Glasgow Outcome Scale score of 5) among controls (90/235; 38%) than among cases (10/49; 21%; p = 0.02). By multivariate analysis, independent predictors of cardiac arrest were pulse oximetry less than 97% on scene (odds ratio, 2.66; 95% CI, 1.03–7.26; p = 0.04), drug poisoning as the cause of convulsive status epilepticus (odds ratio, 4.13; 95% CI, 1.27–13.53; p = 0.02), and complications during early management (odds ratio, 11.98; 95% CI, 4.67–34.69; p < 0.0001). Having at least one comorbidity among cardiac, respiratory, and neurologic (other than epilepsy) conditions predicted absence of cardiac arrest (odds ratio, 0.28; 95% CI, 0.10–0.80; p = 0.02). Conclusions: In patients managed for convulsive status epilepticus, relative hypoxemia, on-scene management complications, and drug poisoning as the cause of convulsive status epilepticus were strong early predictors of cardiac arrest, suggesting areas for improvement. Abstract : Supplemental Digital Content is available in the text.